Stewardship Value of Earnings Components: Additional Evidence on the Determinants of Executive Compensation - Natarajan, Ramachandran (The Accounting Review, 1996)
[This paper investigates the role of components of earnings in CEO compensation contracts. It argues that shareholders will use components of earnings as additional performance measures whenever the components provide information, over and above earnings, about managerial decisions. Results indicate that earnings and cash flow measures together have a better association with cash compensation paid to CEOs of U.S. companies than aggregate earnings alone. The evidence also suggests that current accruals and cash flows from operations are aggregated for performance evaluation. Stewardship value measures are able to explain some of the cross-sectional variation in the weights attached to earnings and working capital from operations. Significant variation in the use of cash flow measures and contract efficiency is detected between the early (1970 to 1979) and late (1980-1988) halves of the sample period.]